PSPO: a framework for cost-effective service placement optimisation during enterprise modernisation on hybrid clouds. (2018) - Ramadoss, Ravikumar; Elango, N.M.; Satheesh, A.; Hsu, Ching-Hsien
An integrated cloud service model utilising both public and private cloud services to provide a holistic deployment of the enterprise applications is the need of the hour. Traditional existing applications getting modernised to meet the high business demands to serve end customers, by adapting technology enhancements towards big data and cloud to achieve the futuristic Service Level Agreements (SLA).Some efforts have been made to model with respect to cost and its impacts, yet the distinctive need is to get a holistic picture of the overall modernisation characteristics. In this paper, we propose a proactive cost optimisation model along with a proposed algorithm to solve some of the key issues towards service placement during enterprise modernisation. The proposed cost optimised algorithm is applied to different scenarios on multiple clouds with enterprise modernisation characteristics. Experimental results derived shown that the proposed work effectively optimises the service placement on multiple clouds.